Photochemical Image Formation Process for High Density Printed Circuit Patterns. (1981) - Takahashi, Katsuhiro; Ikari, Kunihiro; Kano, Jiro; Takamura, Tsutomu; Ueki, Toshihiro; Yamaoka, Tsuguo; Tsunoda, Takahiro
Abstract : A new method for fabricating high density printed circuit boards has been investigated. The procedure used for photoselective metal deposition on the substrate consists of five steps: adhesion treatment, sensitization, nucleation, fog inhibition and electroless metal deposition. An adhesive coated substrate was sensitized by introducing an aqueous solution containig anthraquinone sulfonic acid sodium salts, reducible noble metal salts and alcohol. The sensitized substrate was then exposed through a mask to a u.v. light. The noble metal nuclei produced by exposure were developed by electroless copper deposition after rinsing with aqueous solutions containing complex agents. Electrically-conductive patterns thus obtained can be further intensified by second electroless plate making.